2017
DOI: 10.1038/s41531-017-0032-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial impairment in microglia amplifies NLRP3 inflammasome proinflammatory signaling in cell culture and animal models of Parkinson’s disease

Abstract: The NLRP3 inflammasome signaling pathway is a major contributor to the neuroinflammatory process in the central nervous system. Oxidative stress and mitochondrial dysfunction are key pathophysiological processes of many chronic neurodegenerative diseases, including Parkinson’s disease (PD). However, the inter-relationship between mitochondrial defects and neuroinflammation is not well understood. In the present study, we show that impaired mitochondrial function can augment the NLRP3 inflammasome-driven proinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
184
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(191 citation statements)
references
References 72 publications
7
184
0
Order By: Relevance
“…Although our goal is to investigate the role of the inflammasome-mediated proinflammatory signal in Meth-potentiation of HIV-associated neurotoxicity, little is known about HIV-1 protein as the first signal for the inflammasome activation. LPS is typically used as the first priming signal on microglia for inflammasome studies (Halle et al, 2008; Shi et al, 2012; Sarkar et al, 2017). The process of the LPS-primed NLRP3 inflammasome is well characterized and involved with the transcriptional induction (pro-IL-1β and NLRP3 induction) and multiple posttranslational events (extracellular signal regulated kinase 1 phosphorylation, proteasome inhibition, and NLRP3 deubiquitination) (Juliana et al, 2012; Ghonime et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our goal is to investigate the role of the inflammasome-mediated proinflammatory signal in Meth-potentiation of HIV-associated neurotoxicity, little is known about HIV-1 protein as the first signal for the inflammasome activation. LPS is typically used as the first priming signal on microglia for inflammasome studies (Halle et al, 2008; Shi et al, 2012; Sarkar et al, 2017). The process of the LPS-primed NLRP3 inflammasome is well characterized and involved with the transcriptional induction (pro-IL-1β and NLRP3 induction) and multiple posttranslational events (extracellular signal regulated kinase 1 phosphorylation, proteasome inhibition, and NLRP3 deubiquitination) (Juliana et al, 2012; Ghonime et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that Meth induces the release of damage-associated molecular patterns (DAMPs) such as high mobility group box-a (HMGB1) that indirectly targets the microglia to upregulate IL-1β expression (Colton, 2009). In a recent study focusing on inflammasome activation in Parkinson’s disease, the author discovered that after priming with LPS as first signal, the mitochondrial complex-1 inhibiting pesticide rotenone activated the inflammasome-induced IL-1β release and thus, promote the dopaminergic neurotoxicity (Sarkar et al, 2017). IL-1β is a well-recognized cytokine in the orchestration of CNS inflammation and is associated with elevated risk of drug dependence (Liu et al, 2009; Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, human dopaminergic neuronal cells were cultured with conditioned media from LPS‐primed rotenone‐treated primary microglial cells, which caused NLRP3 inflammasome‐mediated dopaminergic neurodegeneration. Similarly, chronic administration of rotenone in a rodent model of PD activated the NLRP3 inflammasome pathway through microglial mitochondrial dysfunction and induced dopaminergic neuronal cell death . The P2X7 receptor, a known mediator of NLRP3 inflammasome activation and release of cytokines, is ubiquitously expressed in microglia .…”
Section: Nlrp3 Inflammasome‐mediated Inflammatory Pathways In Pdmentioning
confidence: 99%
“…Cell death occurs by proteolytic enzyme caspase 1‐mediated activation of IL‐1β, and IL‐18, followed by subsequent formation of membrane pores and cell lysis, a process called pyroptosis . Several individual studies of in vitro and in vivo models of PD have suggested a clear link between aggregation of α‐synuclein, followed by mitochondrial reactive oxygen species (ROS) generation and cathepsin B release with the activation of microglial NLRP3 inflammation‐mediated pyroptotic death of dopaminergic neurons in the SNpc . On the other hand, a rare single‐nucleotide polymorphism (SNP) of NLRP3 has been reported to decrease the risk of developing PD, which proves the authentication of the role of NLRP3 inflammasome in development of PD .…”
mentioning
confidence: 99%
“…Emerging evidence showed that neuroinflammation and oxidative stress are two pivotal roles in pathophysiological process of postoperative cognitive decline and other neurodegenerative disorders such as Parkinson's disease (PD), Alzheimer's disease (AD, and multiple sclerosis (MS) . An accumulating body of studies indicated that using some anti‐inflammatory or antioxidant interventions, such as anti‐TNF antibody, aspirin‐triggered resolvin D1 (AT‐RvD1) or resveratrol, could inhibit the neuroinflammation and oxidative stress in the models of surgical trauma or neurodegenerative diseases .…”
Section: Introductionmentioning
confidence: 99%